If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 13 = -23 + -10 Reorder the terms: 13 + 2x = -23 + -10 Combine like terms: -23 + -10 = -33 13 + 2x = -33 Solving 13 + 2x = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2x = -33 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = -33 + -13 2x = -33 + -13 Combine like terms: -33 + -13 = -46 2x = -46 Divide each side by '2'. x = -23 Simplifying x = -23
| x2-4/25 | | 87+3(x)=165 | | -5b+11=1-6b | | 3m-2(5m-3)=1 | | x-32=-45 | | 3(x+2)=24-10+x | | 44=-16t^2+32t+6 | | 3(1/3x)-5x=12 | | x/6-3.7=11 | | 3p+10=4 | | 5/7x=50 | | y=7.41-0.14(8) | | -8(x+2)+3(x+5)=-2(x+3)+4(2x-1) | | 8=7.41-0.14x | | 5/13=t-6/3 | | y=7.41-0.14x | | g(3x)=2x^2+x | | 5x+3=20+30x | | 5b=80 | | x^2-28x+11=0 | | 4x^3-9x-12=0 | | 3/5y-6=-9 | | 4.5(z+6)+24.5=7 | | 4x-12+8x=15+12x+5 | | 37+82+a=360 | | d-10=30 | | g(x)=2x^2+x | | 3x+6x-4=36 | | -7x-(24/17)=19 | | 12x=9x | | x=11-7x-8 | | ln(6x)=9 |